2016
DOI: 10.1177/1550059416643824
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative EEG in Children and Adults With Attention Deficit Hyperactivity Disorder

Abstract: In recent decades, resting state electroencephalographic (EEG) measures have been widely used to document underlying neurophysiological dysfunction in attention deficit hyperactivity disorder (ADHD). Although most EEG studies focus on children, there is a growing interest in adults with ADHD too. The aim of this study was to objectively assess and compare the absolute and relative EEG power as well as the theta/beta ratio in children and adults with ADHD. The evaluated sample comprised 30 male children and 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 43 publications
8
56
0
2
Order By: Relevance
“…The comparison between the pups born to control and sleep restricted dams is shown in symbol -for decrease. The level of significance is −p < 0.01. comparable to the increased delta power in the children with attentiondeficit/hyperactivity disorder (ADHD) (Markovska-Simoska and Pop-Jordanova, 2017). An increased delta percentage in sleep is also reported in children with attention deficit disorder (Ramos Platon et al, 1990) which is akin to resting state high delta power in the EEG reported in several studies in the ADHD children (Matsuura et al, 1993;Clarke et al, 1998;Barry et al, 2003).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The comparison between the pups born to control and sleep restricted dams is shown in symbol -for decrease. The level of significance is −p < 0.01. comparable to the increased delta power in the children with attentiondeficit/hyperactivity disorder (ADHD) (Markovska-Simoska and Pop-Jordanova, 2017). An increased delta percentage in sleep is also reported in children with attention deficit disorder (Ramos Platon et al, 1990) which is akin to resting state high delta power in the EEG reported in several studies in the ADHD children (Matsuura et al, 1993;Clarke et al, 1998;Barry et al, 2003).…”
Section: Discussionmentioning
confidence: 90%
“…The reduced delta power and higher percentage of theta, alpha and beta power in the pups of sleep restricted dams on D15 bear close analogy to altered EEG power with significantly reduced percentage of delta power in preterm fetal growth restricted human infants, indicative of delayed brain maturation (Cohen et al, 2018). Sudden reversal in delta power on D20 in the sleep restricted group, on the contrary, can be described as disruption in neuro‐maturational control which is comparable to the increased delta power in the children with attention‐deficit/hyperactivity disorder (ADHD) (Markovska‐Simoska and Pop‐Jordanova, 2017). An increased delta percentage in sleep is also reported in children with attention deficit disorder (Ramos Platon et al, 1990) which is akin to resting state high delta power in the EEG reported in several studies in the ADHD children (Matsuura et al, 1993; Clarke et al, 1998; Barry et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Begleiter and Porjesz 4 have suggested that this may be an electrophysiological index of an imbalance in the excitation–inhibition homeostasis in the cortex, which underlies a predisposition to develop AUD and related disorders. 4,14,20 Further supporting this hypothesis is the association of beta EEG and other disorders characterized by behavioral disinhibition: externalizing behavior in children 19 and adolescents, 7 ADHD, 10,21,22 internet addiction, 8,9 and binge drinking in emerging adults. 23 …”
Section: Introductionmentioning
confidence: 85%
“…A higher Beta frequency amplitude, on the other hand, may indicate increased anxiety, as well as problems with concentration and sleep (Britton et al, 2016;Markovska-Simoska & Pop-Jordanova, 2017).…”
Section: Resultsmentioning
confidence: 99%